2015
DOI: 10.1177/1352458515579443
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive reserve moderates the impact of subcortical gray matter atrophy on neuropsychological status in multiple sclerosis

Abstract: SCGM atrophy occurs in normal controls, but significantly more so in MS. While CPS did not change in normal controls, low cognitive reserve was associated with CPS decline in MS. High cognitive reserve protect MS patients from cognitive decline related to SCGM atrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
37
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 35 publications
5
37
0
3
Order By: Relevance
“…In contrast, the level of formal education had significant influence on the SDMT (p < 0.01) and CVLT (p < 0.05). This effect of protection on the NTs is a replication of previous data widely suggested by other authors 8, 19,25,28,29 . Interestingly, a study performed in the last decade 5 suggested cut-off points for the SDMT accordance with educational level of patients and considered differences of 1, 1.5 and 2 SD below the mean of normal controls as cognitive impairment, reinforcing the importance of the impact of this variable on NTs.…”
supporting
confidence: 90%
“…In contrast, the level of formal education had significant influence on the SDMT (p < 0.01) and CVLT (p < 0.05). This effect of protection on the NTs is a replication of previous data widely suggested by other authors 8, 19,25,28,29 . Interestingly, a study performed in the last decade 5 suggested cut-off points for the SDMT accordance with educational level of patients and considered differences of 1, 1.5 and 2 SD below the mean of normal controls as cognitive impairment, reinforcing the importance of the impact of this variable on NTs.…”
supporting
confidence: 90%
“…Our findings are in line with the well-established concept that the DGM are an early and common site of atrophy in patients with MS [17][18][19][20][21][22][35][36][37][38], which progresses longitudinally [20,21,36,37,[39][40][41]. The magnitude of decreased DGM volumes we demonstrated in our study during the observation period is inline with these previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…GM and white matter (WM) pathology are not necessarily closely coupled [15]. Furthermore, previous studies have shown that the deep gray matter (DGM, i.e., basal ganglia and thalamus) is disproportionately affected as compared to the cortical GM [17] and whole brain [18,19] and such involvement is highly clinically relevant [19][20][21][22]. Regarding the methodology available to assess brain volume loss from MRI CONTACT Rohit Bakshi rbakshi@post.harvard.edu scans, recent data indicate advantages of 3T vs. 1.5T MRI for accuracy and validity [23], which parallels its advantages in assessing lesions [24][25][26].…”
Section: Original Articlementioning
confidence: 99%
“…Interestingly, even though decline in SDMT over 3 years was associated with morphological abnormalities in the thalamus; 102 as a group, MS patients were stable on the test compared to HCs. 103,104 Most notably, the SDMT is not a pure test of processing speed. SDMT performance can be influenced by visual acuity and ocular motor functions, 10,105 and while SDMT is correlated with other processing speed tests, there is undoubtedly some incidental learning of symbol–digit associations, and hence the need for alternate forms.…”
Section: Discussionmentioning
confidence: 99%